PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS IPA PESERTA DIDIK KELAS IV SD KABUPATEN TEMANGGUNG - Tatin Rochana; Yuni Listyoningrum; Daimul Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was carried out to improve the conceptual understanding of fourth grade students at SD N 1 Tleter by implementing the Project Based Learning (PjBL) model. The method used is classroom action research. The subjects of this research were class IV students with a total of 12 students and was carried out in 2 cycles. The data collection method used is test questions to measure students' critical thinking skills and understanding of concepts. The data analysis technique used is descriptive statistics. Based on the results of research that has been carried out by applying the Project Based Learning (PjBL) model to learning during research, it can improve students' critical thinking skills in learning activities in the learning process in cycle I. The class average obtained was 70.83 with the number of students still below the KKM. was 4 people and in the second cycle it increased to 82.5. There is 1 student who has not yet completed.